PERAN PEREMPUAN DALAM POLITIK DEMI MEMPERJUANGKAN KESETARAAN GENDER - Naisya Sahira; Emilia Susanti; Patma Azizah; Sari Nabiila Ahmad (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Women and men should be treated equally regardless of their gender, according to the idea of gender equality. Politics is the act of making decisions collectively in government to accomplish shared objectives.The primary tool for attaining gender equality in politics is women, and this essay examines their vital role in that arena. The patriarchal culture that views itself as the more suitable leader than women presents a number of challenges for women in the political sphere, despite the fact that gender equality is still a developing and deeply ingrained aspect of society. It is then unfair to place women in a competitive position due to the existence of traditional ideas, which can be considered to be highly relevant. Social interactions frequently view women as inferior human beings. The patriarchal culture that views men as holding a higher status than women is to blame for this. This study highlights the different obstacles that women have when trying to participate in politics. This study employs the library research approach, in which the gathered, examined, and comprehended materials are provided in an explanation.